Synthesis and Evaluation of Novel Erucin Analogues as Potential Antitumor Compounds - Shao, Yan-Dong; Song, Huang-Wang; Feng, Wen; Wang, Xiang-Hui; Shi, Zai-Feng; Wu, Lu-Yong; Chen, Guang-Ying; Lin, Qiang (Letters in Organic Chemistry, 2018)
Background#154;Several studies have shown excellent antitumor activity of erucin, but there are few studies on its analogues. The aim of the study involves the synthesis and the antitumor activities of novel erucin analogues. Ten novel erucin analogues were synthesized and evaluated for their efficacy as antitumor agents. Methods: Ten novel erucin analogues were synthesized by using 1, 4-dibromobutane and potassium phthalimide as starting materials, and the antitumor activities in vitro was screened against breast cancer cells (MCF-7), cervical cancer cells (HeLa-229) and lung cancer cells (A549). Results: The structures of these novel compounds were confirmed by 1H NMR, 13C NMR and elemental analysis. The preliminary bioassay results demonstrated that all of the tested compounds showed potent antitumor activities. Among these compounds, compound 6b showed the best inhibitory effect against MCF-7 with IC50 value of 0.46 μM and A549 with IC50 value of 0.44 μM. Compound 6f also displayed the best inhibitory effect against HeLa-229 with IC50 value of 0.32 μM. Conclusion: Synthesis and screening of antitumor activities were performed for a novel series of erucin analogues. All of the synthetic compounds showed potent antitumor activities against breast cancer cells (MCF-7), cervical cancer cells (HeLa-229) and lung cancer cells (A549). Compounds 6b and 6f were found to be the most active against most of the tested cancer cells.
Keywords: breast cancer cells